Effect of refrigeration of blood samples in lithium-heparin tubes on QuantiFERON TB Gold Plus test result. Issue 3 (March 2020) - Uwamino, Yoshifumi; Sakai, Akiko; Nishimura, Tomoyasu; Noguchi, Masayo; Uno, Shunsuke; Fujiwara, Hiroshi; Mori, Masaaki; Wakui, Masatoshi; Murata, Mitsuru; Hasegawa, Naoki
Abstract: The QuantiFERON TB Gold Plus (QFT-Plus) test is a newly approved interferon-gamma releasing assay test for detecting latent tuberculosis. Although blood samples for QFT test can be refrigerated for 48 h in lithium-heparin tubes according to package inserts, no published data are available on the effects of sample refrigeration on the test results. We conducted a clinical study that aimed to elucidate whether sample refrigeration for 48 h affects QFT-Plus test results. We collected 2 blood samples each from 40 participants for QFT-Plus; one sample was refrigerated before incubation for QFT-Plus assay, while the other sample was incubated soon after collection and treated as control. After comparing QFT-Plus test results of refrigerated samples and control samples, the concordance rate and kappa coefficient between them were 95% and 0.90, respectively. Thus, blood samples for QFT-Plus test can be refrigerated for 48 h in lithium-heparin tubes without influencing the test results.